Study on The Consumption of Milk and Dairy Products in Romania - Violeta GAGU (LEOCĂ); Gheorghe Adrian ZUGRAVU (Communications of International Proceedings, 2022)
This article proposes a scientific assessment of the consumption of milk and dairy products in Romania. The diversity of the thematic area of the study will allow the realization of some in-depth analyzes on economic and social situation of the population and households. Materials and methods used for research consist of treaties and scientific articles on the consumption of milk and dairy products, data on their production and consumption, statistical databases. The quality of milk and dairy products have direct consequences on the health of the consumer, good agricultural practice, good hygienic practice, good production practice must be observed throughout the food chain.
Keywords: consumption; milk; dairy products; quality; factors